The Influence of Learning Discipline on the Learning Achievement of Class X Students of Office Management and Business Services - Annisa, Annisa; Nasrullah, Muh.; Arhas, Sitti Hardiyanti (International Journal of Administration and Education, 2025)
Learning discipline is an attitude of obedience and obedience to the values that are believed in, including doing certain work that is his responsibility to adapt and gain changes in insight and behavior from his disciplinary experience. This study aims to find out the description of the learning discipline of class X students of the MPLB Department of SMK Negeri 4 Makassar and the influence of learning discipline on the learning achievement of students in class X of the MPLB Department of SMK Negeri 4 Makassar. The purpose is to find out the description and influence of learning discipline on the learning achievement of Class X students of the MPLB Department of SMK Negeri 4 Makassar. This type of research is quantitative. This research was carried out at SMK Negeri 4 Makassar. This research was conducted from April to May 2024. The sample used was 63 people. Data collection techniques are in the form of observations, questionnaires, and documentation. Data analysis techniques are in the form of validity tests, reliability tests, normality tests, descriptive analysis, T (partial) tests, and simple linear regression analysis. The results of the study showed that the indicators used for each of these variables showed where the picture of learning discipline was in the very good category. Based on the T test, it was concluded that there was a significant influence of learning discipline on the learning achievement of class X students of the MPLB Department of SMK Negeri 4 Makassar was declared accepted. This research can be used to improve learning achievement from the aspect of resources.